In Situ Nuclear Morphology Measurements Using Light Scattering as Biomarkers of Neoplastic Change in Animal Models of Carcinogenesis. Issue 6 (4th June 2013) - Wax, Adam; Pyhtila, John W.
Abstract : Light scattering spectroscopy measurements can be used to determine the structure of tissue samples. Through refined data acquisition and signal processing techniques, quantitative nuclear morphology measurements may be obtained from light scattering data. These data have been used primarily as a biomarker of neoplastic change in a wide range of settings. Here, we review the application of light scattering to assessing the health status of tissues drawn from animal models of carcinogenesis, in particular, the rat esophagus and the golden Syrian hamster trachea carcinogenesis models. In addition, we present results from ex vivo human tissues to demonstrate the relevance of the use of animal models which are excellent surrogates for several human cancers. These models provide the opportunity to develop biomarkers and test chemopreventive and therapy strategies before application in humans.